Influence of grip strength with different body Postures in collegiate - MALARVIZHI.D,; VIDHYA.G,; DHINESH.A.M,; SIVAKUMAR.V.P.R., (International Journal of Pharma and Bio Sciences, 2017)
The objective of the study was influence of grip strength with different body postures.Study design was Non-Experimental, study type was observational. Inclusion criteria were both males and females, age between 17 to 22 years.30Subjects were selected according to inclusion and exclusion criteria.Grip strength was measured in three main postures standing ,sitting and squatting, forearm in mid prone position and elbow 90 degree flexion for right hand, Grip span variations as 1cm, 2cm, 3cm and 4cm was conducted by using a hand held dynamometer.Thestatistical analysis was done(ANOVA).The results of the study showed that Mean and S.D values were in standing was 15.09±6.47,sitting was 14.93±6.25 and squatting was 16.5±7.45.There was close association of hand grip strength between standing, sitting and squatting.The study concluded that there was no difference in the force production of grip strength in different postures for right hand.